Nursing Innovation to Reduce Anxiety in Newly Diagnosed Endstage Kidney Disease Patients Undergoing Hemodialysis: Literature Review - Fathul Muin; Arif Setyo Upoyo (Indonesian Journal of Global Health Research, 2026)
End-stage renal disease (ESRD) patients who have just started hemodialysis frequently experience high levels of anxiety caused by lifestyle changes, uncertain prognosis, and the burden of long-term therapy. Anxiety negatively impacts treatment adherence and quality of life, highlighting the need for effective nursing interventions to support psychosocial well-being. Purpose: This systematic literature review aimed to identify and analyze evidence-based nursing innovations that are effective in reducing anxiety among newly diagnosed ESRD patients undergoing hemodialysis. Methods: A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines for studies published between 2015 and 2025. Literature searches were performed in Scopus, PubMed, ScienceDirect, and Google Scholar using combinations of the keywords “end-stage renal disease,” “hemodialysis,” “anxiety,” “nursing intervention,” “cognitive behavioral therapy,” and “psychosocial intervention.” From 4,301 records initially identified, seven studies met the inclusion criteria, consisting of four randomized controlled trials (RCTs), two RCT protocols, and one pilot study. Data were synthesized narratively to evaluate the effectiveness of nursing and psychosocial interventions in reducing anxiety among newly diagnosed ESRD patients undergoing hemodialysis. Results: The review found that Cognitive Behavioral Therapy (CBT) was consistently effective in reducing anxiety and depressive symptoms, particularly when combined with resilience-based models or mindfulness techniques. Advance Care Planning (ACP) interventions improved patients’ emotional acceptance and psychological adjustment, although their direct effect on anxiety reduction was limited. Technology-based interventions, including internet-based CBT (iCBT) and guided problem-solving therapy (PST), demonstrated strong potential as flexible, accessible, and cost-effective approaches. In addition, a pilot study utilizing virtual reality (VR) during hemodialysis procedures reported reductions in procedural pain and anxiety. Conclusion: Evidence-based nursing innovations incorporating CBT, ACP, digital interventions, and virtual reality show considerable potential in reducing anxiety among patients newly undergoing hemodialysis. These findings emphasize the critical role of nurses as psychosocial facilitators and support the integration of holistic, patient-centered, and technology-driven care models into routine hemodialysis practice.